MODEL KERUKUNAN UMAT BERAGAMA DI DUSUN SUSURU - Abdul Jamil Wahab (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2019)
Being harmony in social and religious life has not perfectly built in lndoensia. The social relationship between religions or even etnics haven't shape yet in very proper form, the conflict potencially appear betwen them that become a basic reason and an interesting motive to study about Dusun Susuru as an exception; Dusun Susuru is a remote village and well known as multi religious, people can live hand in hand and harmony there. Some religious social activities are also carried out together. This study prefer to use qualitative method and from that kind of method we found that the religious groups there such as Islam, Katolik, Kritsten, and Penghayat lived in one village, one worship place, and they live also closely as neighbour. Some social and religious activities done togetherly, for example: establishing house of worship, tahlilan, accepting equal rights inheritance and so on. All things that has been mentioned above is a portrait of the social interaction that have described as a mutual pattern between each religions and each etnic which is beyond the tolerance concept in common. This religious harmony in portrait could be a best practice for managing inter religious harmony in another places. Keywords: Dusun Susuru, multireligious, Penghayat.